Common familial risk factors for schizophrenia and diabetes mellitus. (May 2016) - Foley, Debra L; Mackinnon, Andrew; Morgan, Vera A; Watts, Gerald F; Castle, David J; Waterreus, Anna; Galletly, Cherrie A
Objective: The co-occurrence of type 2 diabetes and psychosis is an important form of medical comorbidity within individuals, but no large-scale study has evaluated comorbidity within families. The aim of this study was to determine whether there is evidence for familial comorbidity between type 2 diabetes and psychosis. Method: Data were analysed from an observational study of a nationally representative sample of 1642 people with psychosis who were in contact with psychiatric services at the time of survey (The 2010 Australian National Survey of Psychosis). Participants were aged 18–64 years and met World Health Organization's International Classification of Diseases, 10th Revision diagnostic criteria for a psychotic disorder (857 with schizophrenia, 319 with bipolar disorder with psychotic features, 293 with schizoaffective disorder, 81 with depressive psychosis and 92 with delusional disorder or other non-organic psychoses). Logistic regression was used to estimate the association between a family history of diabetes and a family history of schizophrenia. Results: A positive family history of diabetes was associated with a positive family history of schizophrenia in those with a psychotic disorder (odds ratio = 1.35, p  = 0.01, adjusted for age and gender). The association was different in those with an affective versus non-affective psychosis (odds ratio = 0.613, p  = 0.019, adjusted for age and gender) and was significant only in those with a non-affective psychosis, specifically schizophrenia (odds ratio = 1.58, p  = 0.005, adjusted for age and sex). Adjustment for demographic factors in those with schizophrenia slightly strengthened the association (odds ratio = 1.74, p  = 0.001, adjusted for age, gender, diagnosis, ethnicity, education, employment, income and marital status). Conclusion: Elevated risk for type 2 diabetes in people with schizophrenia is not simply a consequence of antipsychotic medication; type 2 diabetes and schizophrenia share familial risk factors.